Cholelithiasis - current knowledge about one of the most common diseases of the digestive system - Demidowicz, Gabriela; Lasota, Nina; Trąbka, Natalia; Younes, Martyna; Kowalczyk, Klaudia; Cichoń, Katarzyna; Chyćko, Małgorzata; Czarnota, Julia; Wiśniewski, Wojciech; Lambach, Maciej (Journal of Education, Health and Sport, 2023)
Introduction: Cholelithiasis is one of the most common diseases of the digestive system and thus the most common cause of hospitalization in gastroenterology. According to the European Association for the Study of the Liver (EASL), it affects up to 20% of the European population and about 10-20% of the Polish population, and the number of patients is constantly increasing. This may be related to the growing problem of obesity and the widespread use of ultrasonography. The disease is also becoming more common in children and adolescents. The costs of gallstone diagnosis and treatment cause a huge financial burden on the health care system. As such, it is a public health issue that deserves more attention. Aim of the study: The aim of this review is to present current and the most important information about cholelithiasis – to determine the association between prevention and cholelithiasis, describe diagnosis, treatment and complications. Materials and methods: The review was based on the analysis of materials collected in the „Pubmed” database, Google Scholar, European Society for the Study of the Liver guidelines (EASL), books and other scientific articles. The search was performer using the key words: „cholelithiasis”, „cholelithiasis treatment”, „cholelithiasis diet”, „gallstone disease”,” gallstones”, „cholelithiasis etiology”, „Biliary Colic” Summary: Cholelithiasis is currently the most common disease of the bile ducts. The increasing incidence of patients with gallstones should contribute to the increased interest in this disease.